2016
DOI: 10.1111/tri.12750
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized composite allotransplantation: a closer look at the banff working classification

Abstract: SUMMARYThe first Banff vascularized composite allotransplantation meeting was held in 2007 to standardize criteria for the characterization and reporting of severity and types of rejection. As a result, the 2007 Banff VCA working classification for skin allograft pathology was formalized and now serves as the standard for diagnosis of VCA rejection. Similar to other working classification systems, strengths and limitations have been identified including the adequacy of the specimen, the definition of severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
(65 reference statements)
1
36
0
Order By: Relevance
“…Also, the routine 4 mm punch skin biopsy does not assess deeper allograft tissues for rejection. The histological assessment might be additionally prone to intra- and interobserver variability, since the differentiation between “mild” (grade I) and “moderate” (grade II) perivascular inflammatory infiltrate is not objectively defined 15 . Last but not least, the clinical relevance of mild forms of rejection (grade I) by Banff grading is unclear too and justifies the question whether grade I rejections in face transplantation should be treated 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the routine 4 mm punch skin biopsy does not assess deeper allograft tissues for rejection. The histological assessment might be additionally prone to intra- and interobserver variability, since the differentiation between “mild” (grade I) and “moderate” (grade II) perivascular inflammatory infiltrate is not objectively defined 15 . Last but not least, the clinical relevance of mild forms of rejection (grade I) by Banff grading is unclear too and justifies the question whether grade I rejections in face transplantation should be treated 51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, skin biopsy is associated with morbidity to the patient, including scarring, bleeding or infection, hence it is not favorable for frequent monitoring. Furthermore, the Banff grading of skin rejection is semiquantitative, might be prone to intra- and interobserver variability, and lacks a correlation to treatment response 12 15 . Thus, strategies to establish non-invasive monitoring, such as from blood samples, are very desirable for the clinical management as well as to define the best treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…5,[9][10][11] The classification has been clinically useful in the diagnosis of rejection, however, the need for characterization of the pathologic features and a better understanding of mechanisms remain. 12,13 The findings in this study highlight the potential usefulness of a systematic approach to evaluation of rejection in allograft biopsies where pathologic patterns may overlap or not meet qualitative characteristics. The richness of this data allows for better clinical or research correlation and can give insights into the varied pathogenesis of rejection in VCA (e.g., epidermal vs. vascular).…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to the high incidence of CMR, acute antibody-mediated rejection (AMR) is rarely observed in VCA (10, 2123). Weissenbacher et al (24) reported one case of AMR and recently reviewed the literature (25).…”
Section: Introductionmentioning
confidence: 99%